P320 Workplace bulling, perceived stress, and sickness absence. (1st September 2016) - Grynderup, Matias Brødsgaard; Nabe-Nielsen, Kirsten; Lange, Theis; Conway, Paul Maurice; Bonde, Jens Peter; Francioli, Laura; Garde, Anne Helene; Kaerlev, Linda; Rugulies, Reinar; Vammen, Marianne Agergaard; Hogh, Annie; Hansen, Åse Marie
Abstract : Background: Workplace bullying is a severe stressor that is related to numerous adverse outcomes, such as poor health and low quality of life. Previous studies have shown that bullying is a strong predictor of long-term sickness absence that can have substantial costs for both society and the individual. A commonly used definition of bullying is when an individual, over a prolonged period of time, such as six months, perceives him/herself as being exposed to negative acts from superiors or co-workers that it is difficult to defend one-self against. The causes of long-term sickness absence are multifactorial. One possible pathway linking workplace bullying and sickness absence is through chronically increased levels of perceived stress. Objective: To examine if perceived stress mediated the association between workplace bullying and subsequent long-term sickness absence. Methods: The PRISME cohort was established in 2007 and re-examined in 2009. Questionnaire data about workplace bullying (self-labelling question) and perceived stress (Cohen's perceived stress scale) were obtained from 4114 individuals. Participants were followed in registers on long-term sickness absence (≥30 consecutive days of sickness absence). Results: We had 4, 114 participants with no history of long-term sickness absence in the previous two years contributing 6, 331 observations in 2007 and/or 2009, giving a total of 6331 observations of which 430 were among workplace bullied. Workplace bullying was associated with subsequent sickness absence (OR = 2.05; 95% CI: 1.57–2.65) and concurrent high perceived stress levels (OR = 2.34; 95% CI: 1.86–2.96). A high perceived stress level was also associated with subsequent sickness absence (OR = 1.33; 95% CI: 1.13–1.56). Perceived stress explained 13% (95% CI: 6–23%) of the total association between bullying and sickness absence. Conclusions: The association between workplace bullying and subsequent long-term sickness absence may be partially mediated by perceived stress.